The Effect of Employee Engagement and Work Motivation on Employee Discipline of The Southeast Sulawesi Provincial Industry and Trade Office - Husain, Asjain; Kalsum, Ummy; Tambunan, Rince (International Journal of Management and Education in Human Development, 2024)
This study aims to analyze and explain: (1) the influence of employee engagement and work motivation simultaneously on employee work discipline at the Industry and Trade Office of Southeast Sulawesi Province, (2) the influence of employee engagement on employee work discipline at the Industry and Trade Office of Southeast Sulawesi Province, and (3) the influence of work motivation on employee work discipline at the Industry and Trade Office of Southeast Sulawesi Province. The research design used in this study is explanatory research. The population of this study were employees with the status of State Civil Apparatus (ASN) at the Industry and Trade Office of Southeast Sulawesi Province. This study uses the census or complete enumeration method, or this study does not use samples so that sampling techniques are not needed. so that the respondents in this study were 70 employees. The results of the study indicate that: (1) Employee engagement and work motivation simultaneously have a positive and significant effect on employee work discipline at the Industry and Trade Service of Southeast Sulawesi Province. Based on the F test with F count (91.601) > F (0.05; 2.70) (3.1504) and a rho sig. value of 0.000 < 0.05, (2) Employee engagement has a positive and significant effect on employee work discipline at the Industry and Trade Service of Southeast Sulawesi Province. Based on the t-statistic probability test, with t count (2.797) > t (0.025; 70) (1.994) and a rho value of 0.007 < 0.05, and (3) Work motivation has a positive and significant effect on employee work discipline at the Industry and Trade Service of Southeast Sulawesi Province. Based on the t-statistic probability test, with t count (5.241) > t (0.025; 70) (1.994) and rho value of 0.000 < 0.05.